(untitled) (BIRDEM Medical Journal, 2022)
Background: Patients with type 2 diabetes mellitus (T2DM) pass through pre-diabetic stages and during diagnosis, half of them may have different complications including diabetic nephropathy. Hypertension has adverse impacts on diabetic nephropathy. We aimed to evaluate the risk factors for diabetic nephropathy among newly detected T2DM patients with normal blood pressure. Methods: A case-control study was done at a tertiary care hospital in Dhaka, Bangladesh from January 2018 to June 2019. Newly detected (<3 months), adult ( ³18 years), T2DM patients, who underwent tests for urine albumin-to-creatinine ratio (UACR), at least twice, 6-weeks apart, were included in this study. Patients with hypertension, known kidney disease, features of glomerulonephritis, systemic diseases including systemic lupus erythematosus and vasculitis, history of recent fever and exercise, urinary tract infection and pregnancy were excluded. Patients with UACR ³30 mg/g in at least two samples were cases and those with UACR <30 mg/g were controls. Results: Among the total 135 patients, 27 were cases [moderately increased proteinuria (previously, microalbuminuria) (UACR 30–299 mg/g) = 25 and severely increased proteinuria (previously, overt proteinuria) (UACR ³300 mg/g) = 2] and 108 were controls. Multivariate logistic regression revealed that family history of diabetes (OR=2.13; 95% CI, 1.412 to 4.216, p=0.003) and diabetic nephropathy (OR=3.31; 95% CI, 2.145 to 5.249, p=0.001), smoking (OR=3.11; 95% CI, 2.234 to 4.123, p=0.003), dyslipidaemia (OR=2.14; 95% CI, 1.363 to 3.324, p=0.005) and diabetic retinopathy (OR=6.23; 95% CI, 4.197 to 9.464, p=0.004) were significant risk factors. Conclusion: We concluded that, family history of diabetes and diabetic nephropathy, smoking, dyslipidaemia and diabetic retinopathy appeared as significant risk factors for diabetic nephropathy among newly diagnosed T2DM patients with normal blood pressure. BIRDEM Med J 2022; 12(2): 152-157